(untitled) (LEARNing Landscapes, 2013)
With the growing acceptance of American Sign Language (ASL) as a true language comes increasing possibility for incorporating it into the classroom, especially for visual learners. While children in general may benefit from ASL, early exposure to ASL is particularly important for Deaf and Hard of Hearing children (D/HH). In this article, we summarize research on the impact of an educational media series in ASL on early language and literacy development, provide research-based strategies for utilizing visual language and visual strategies during literacy activities, and offer recommendations for teachers about incorporating research-tested educational media in the classroom.